The Stockholm Study: Over 30 years' Observation of the Effect of Oral Infections on Systemic Health - Jukka H. Meurman; Birgitta Söder (MDPI AG, 2022)
The Stockholm Studies are a series of investigations started in 1985 and still ongoing. Out of 105,798 inhabitants, aged 30 and 40 years and living in the greater Stockholm area in Sweden, 3273 subjects were randomly selected. Of them, 1676 were clinically examined focusing on oral health. The subjects were then followed up using national population and health registers in order to study associations between oral health parameters and systemic health outcomes and finally death. The 35 years of observation provides unique possibilities to analyze, for example, how periodontitis links to a number of systemic health issues. The results have consequently provided numerous new associations and confirmed earlier observations on how poor oral health is associated with heart diseases and cancer.